Are patrons using the research books? A new approach to approval plan assessment. (5th July 2021) - Attebury, Ramirose Ilene
Abstract : Purpose: The purpose of this study is to present findings of an approval plan assessment project, which analyzed circulation statistics for four Gobi Select designations: research essential, research recommended, basic essential and basic recommended. Design/methodology/approach: This study approaches approval plan assessment by analyzing three years of circulation statistics to determine which, if any, of the Gobi Select designations circulated the most. Findings: This study reveals that books designated as "basic essential" have circulated at higher rates than other designations. Originality/value: To the best of the author's knowledge, no other studies have made use of Gobi Select designations to analyze circulation statistics for books obtained on an approval plan.